KEWENANGAN PENCATATAN NIKAH MELALUI PENGHULU DAN KEPALA KUA DALAM PERSPEKTIF PERATURAN MENTERI AGAMA DENGAN PERATURAN PENDAYAGUNAAN APARATUR NEGARA - Achmad Murtadho Usman (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2021)
Marriage registration for Muslims is carried out by Marriage Registration Officer (PPN). Minister Religion Regulation (PMA) Number 11 2007 concerning Marriage Registration Article 2 Paragraph (1) mentions Head of KUA as PPN. Meanwhile, Ministe State Apparatus Empowerment Regulation Number: Per/62/M. PAN/6/2005 concerning Functional Position Penghulu Article 1 Paragraph (1) states that Penghulu also PPN. Serious problems related to authority Penghulu caused by mention Penghulu and Head of KUA as PPN, this makes authority Penghulu as functional give Prealable authority which authority to carry out decisions taken without asking for prior approval from agency or individual, which this can have an impact on validity marriage book by penghulu or head of KUA. This research uses empirical juridical research and uses a qualitative approach. Results analysis, that in practice registering marriages at KUA of Sukun Subdistrict, Malang City, conclusions: First, functions and authorities role Penghulu as PPN to carry out munakahat legal fatwas, mu’amalah guidance, as advisory supervision and marriage consultation or reconciliation. role Head of KUA as PPN supervise implementation duties Penghulu and Assistant PPN, reporting marriage registration to Regency/City Ministry of Religion, as guardian adlol or guardian judge and signing examination, agreements and events marriage certificates, divorce, and reconciliation. Second,implementation, namely: mandate Head of KUA to Penghulu responsibility and accountability Head of KUA, Head of KUA can give mandate to Penghulu carry out tasks in some of his working areas, and role of Penghulu as form representative Head of KUA when unable to attend meeting. wedding ceremony. Third, supporting factors include: understanding importance registering marriages, Penghulu at District KUA fulfills human resources and role Head of KUA in management and coaching. Inhibiting factors: level of understanding regulations not optimal, human resources KUA employees still lacking, clash mentioning Penghulu and Head of KUA as PPN, and lack supervision from BIMAS Islam.